Valor agregado em produtos e serviços em concessionários de máquinas agrícolas no Brasil utilizando o método AHP - Gabbi, Adriana (2017)
The objective of the present study was to identify which criteria lead customers of agricultural machinery dealers to perceive added value in purchased products and services. Through a multi-approach study with a combined approach, examining three agricultural machine dealers located in Brazil and identifying three main customers of these machines. In this stage, we conducted interviews through the application of semi-structured questionnaires and focus groups have been carried out with the clients to apply the multi-criteria AHP method. From the application of the questionnaire, we identified the main value-added criteria applied to products and services, verified in the main literature on the theme. We had identified the following value-added criteria: long-term relationship, brand, quality, price, trust and post-sales, are adherent to the answers of managers, and if they identify other criteria, different from those presented. Then, the application of the AHP, opportune to acknowledge the opinion of decision makers on what the main criteria they consider as value added products and services and that directly influence the purchase decision. In the sequence, we analysed the criteria perceived as the added value of goods and services offered by agricultural machinery dealers, analysing and comparing the most important ones in order of relevance, so that companies of the agricultural segment could use the identified results to formulate their strategies with clients. At the end of the study, the post-sale criteria (28.41%), confidence (28.08%), LP (15.15%), quality (13.81%), price (9.44%) and brand (5.11%), are those that customers perceive as added value to products and services and are considered as a priority when purchasing decision.